Current Status of Threatened Plant Collections in Cibodas Botanical Garden Based on IUCN Red List - Vandra Kurniawan; Dwinda Mariska Putri; Muhammad Imam Surya (Jurnal Penelitian Kehutanan Wallacea, 2020)
One of the main task of Cibodas Botanical Garden (CBG) is to conserve the Indonesian plants species. Moreover, the preservation and enrichment of threatened plant collections based on IUCN red list categories became an important programme for plants conservation in CBG. The aims of this study are to inventory threatened plant collections and to reviewthe status of CBG threatened plant collections. List of threatened plantcollections was gathered from SINDATA, a system developed by CBG. The collection, was reviewed by inspecting current collections in CBG. Literature study was done to review the conservation status of the threatened plant collections. The conservation status was checked in IUCN red list website. The results shown that CBG had collected 86 species of threatened plants, which is 13 Critically Endangered (CR) species, 39 Endangered (EN) species, and 34 Vulnerable (VU) species.Critically endangered category consists of 13 species belong to 8 familiesand 10 genus. Endangered category consists of 39 speciesbelong to 17 familiesand 34 genus. Vulnerable category consists of 34 species belong to 27 familiesand28genus.The largest collections of threatened species was genus Nepenthes, which is 16% (14 species) from the total threatened species in CBG..Furthermore, CBG had succeeded in collecting 40speciesofIndonesiannative plants in which Dipterocarpaceae specieswere dominate the collection with 7 species.These species are listed as critically endangered (3 species) and endangered (4 species).